2018
DOI: 10.1142/s1793431118410038
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Surface Fault Displacement by High Performance Computing

Abstract: Reliable estimation of surface fault displacements is crucial to the safety of nuclear power plant facilities. It is necessary to develop a numerical method for the estimation. In the study, we develop a finite element method in which the following two functions are implemented: (1) a symplectic time integration of an explicit scheme to properly conserve the energy of the system; and (2) rigorously formulated joint elements of high order. The finite element method is enhanced with parallel computing capability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…This is extremely important for the estimation of ∆ c . Sawada et al [13] demonstrated that the calculated ∆ c and δ from quasi-static simulations were close to those calculated using dynamic simulations with damping and proposed the use of quasi-static simulations for capacity computing. Therefore, quasi-static simulations were adopted in this study.…”
Section: Estimation Of Fault Displacementmentioning
confidence: 79%
See 3 more Smart Citations
“…This is extremely important for the estimation of ∆ c . Sawada et al [13] demonstrated that the calculated ∆ c and δ from quasi-static simulations were close to those calculated using dynamic simulations with damping and proposed the use of quasi-static simulations for capacity computing. Therefore, quasi-static simulations were adopted in this study.…”
Section: Estimation Of Fault Displacementmentioning
confidence: 79%
“…We implemented joint elements using a nonlinear spring-type constitutive equation to represent fault movement [12,13]. The constitutive equation for the shear movement of the joint element is defined as follows (see Figure 4):…”
Section: Fem For the Fault Displacement Problemmentioning
confidence: 99%
See 2 more Smart Citations